The impact of recent Irish higher education policy on a Catholic University-level College of Education and the Liberal Arts. Issue 1 (2nd January 2020) - Collins, Paul
Abstract : The Irish Department of Education and Skills' National Strategy for Higher Education to 2030 (2011; better known as the 'Hunt Report') and subsequent policy initiatives continue to impact on the Republic's HE sector. This paper examines the effect of such initiatives on Mary Immaculate College, a third-level Catholic College of Education and the Liberal Arts with campuses in Limerick and Thurles. Three facets of the College that have been significantly affected by system policy are considered: first, looking inwards, MIC as an organisation; second, looking outwards, the College's place in the regional and national HE landscape; and finally, looking around globally, MIC as a Catholic institution. This last facet of the College – its Catholic ethos – has been central to MIC's identity since the 1890s, and while running counter to the values espoused by the National Strategy, it nevertheless enhances the College's distinctiveness in the current Irish HE landscape.